Alarming Reports : Communicating Conflict in the Daily News. - Arno, Andrew (Anthropology of media ;, 2009)
News stories provide an essential confirmation of our ideas about who we are, what we have to fear, and what to do about it: a marketplace of ideas, shopped by rational citizen decision makers but also a shared resource for grounding our contested narratives of identity in objective reality. News as a fundamental social process comes into being not when an event takes place or when a report of the event is created but when that report becomes news to someone. As it moves off the page into the community, news discovers through its interpretations its reality in the lives of the consumers. T.